2006
DOI: 10.1111/j.1467-7687.2006.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of divided attention on inhibiting the gravity error

Abstract: Children who could overcome the gravity error on Hood's (1995) tubes task were tested in a condition where they had to monitor two falling balls. This condition significantly impaired search performance with the majority of mistakes being gravity errors. In a second experiment, the effect of monitoring two balls was compared in the tubes task and a spatial transposition task not involving gravity. Again, monitoring two objects produced impaired search performance in the gravity task but not in the spatial tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…For example, when they see a ball dropped through the left chimney of the apparatus shown in Figure 1, they will incorrectly search for the ball in the left cup, even though they can see the opaque tube that connects the left chimney to the right cup. In a series of seminal studies, Hood and his colleagues have shown that this error represents a “gravity bias:” The error persists even after multiple trials (Hood, 1995), it can re-emerge in older children under conditions of divided attention (Hood, Wilson & Dyson, 2006), and it is not caused by mere adjacency considerations because the analogous error is not obtained if the ball travels in the upward direction (Hood, 1998). …”
Section: Studymentioning
confidence: 99%
“…For example, when they see a ball dropped through the left chimney of the apparatus shown in Figure 1, they will incorrectly search for the ball in the left cup, even though they can see the opaque tube that connects the left chimney to the right cup. In a series of seminal studies, Hood and his colleagues have shown that this error represents a “gravity bias:” The error persists even after multiple trials (Hood, 1995), it can re-emerge in older children under conditions of divided attention (Hood, Wilson & Dyson, 2006), and it is not caused by mere adjacency considerations because the analogous error is not obtained if the ball travels in the upward direction (Hood, 1998). …”
Section: Studymentioning
confidence: 99%
“…Prolonged looking in young infants, a phenomenon termed by some as 'obligatory attention', is postulated to result from the emergence of neural processes that inhibit peripheral eye movements. Hood et al [50,51] have suggested that prolonged looking may be related to infant inability to disengage from a salient fovea stimulus. The inability to disengage fixation in such infants may be an immature pattern reminiscent of the obligatory attention noted in very young infants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they repeatedly commit the ''gravity error'' in spite of negative feedback on many trials (Hood, 1995(Hood, , 1998Hood, Santos, & Fieselman, 2000;Hood, Wilson, & Dyson, 2006). Further evidence for the robustness of this error comes from comparative studies.…”
Section: Introductionmentioning
confidence: 94%
“…By implication, dividing children's attention interfered with their ability to inhibit the prepotent response, which in turn led them to revert to the systematic gravity error (Hood et al, 2006). In a different study, 4-, 5-, and 7-year-olds who could accurately solve the tubes task were asked to approach an empty cup.…”
Section: Introductionmentioning
confidence: 99%